WAIS Divide Ice Core CO2 - Brook, Edward J.; Marcott, Shaun (IEDA: US Antarctic Program Data Center, 2015)
The data are measurements of carbon dioxide (CO2) from the WAIS Divide Ice Core, WDC06A, Antarctica.